Penerapan UU No. 8 Tahun 2016 Tentang Disabilitas Pada Pelayanan Perbankan Syariah - Ainulyaqin, MH; Rakhmat, AS; Achmad, LI; A, Yudianto; Badriyah, S (Jurnal Ilmiah Ekonomi Islam, 2024)
The purpose of this study was to identify the barriers to the implementation of Law No. 8 of 2016 on Disabilities and the appropriateness of its application for the blind customer service at PT. BSI KCP East Bekasi. This study employed a qualitative methodology in a field setting with a focus on social construction phenomenology. The methods used to collect the data were observation, interviews, and documentation. The Bank Operation Service Manager and many Service Staff of PT. BSI KCP East Bekasi were the study's subjects. The findings of this study showed that providing bank services to blind clients in PT BSI KCP East Bekasi complied with the requirements of Article 9 Point (e) of Law no. 8 of 2016 on Disabilities. This form of service is based on making blind bank customers also as priority customers. To provide assistance and special services when opening accounts and cash withdrawals, as well as allowing blind customers to use accessibility owned by banks in the form of mobile banking and ATM machines with conditions for assistance from the family. Regarding the application of accessibility, Article 18 points (a) and (b) of Law no. 8 of 2016 on Disability, banks have several factors of accessibility barriers specifically for the visually impaired, both internally and externally, however, related to these obstacles, banks continue to provide solutions to provide satisfaction to blind customers.